2015
DOI: 10.1007/s00482-015-0006-4
|View full text |Cite
|
Sign up to set email alerts
|

Schmerzmessung bei kognitiv beeinträchtigten Patienten mit der Doloshort-Skala

Abstract: The Doloshort scale is a well suited measurement instrument for the evaluation of pain in cognitively impaired patients. Because of the short form only simple instructions are necessary and it has a high acceptance with users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…A summary of the excluded tools is provided in Table S3. Twelve of the studies excluded at full-text review reported on psychometric properties of translated versions of the included tools: Doloplus-2 (Japanese, 54 Chinese, 55,56 Norwegian, [57][58][59] French, 60,61 German, 62 Persian, 63 Dutch 64 ) and Paediatric Pain Profile (PPP) (Brazilian Portuguese 65 ). These articles are summarized in Table S4.…”
Section: Search Resultsmentioning
confidence: 99%
“…A summary of the excluded tools is provided in Table S3. Twelve of the studies excluded at full-text review reported on psychometric properties of translated versions of the included tools: Doloplus-2 (Japanese, 54 Chinese, 55,56 Norwegian, [57][58][59] French, 60,61 German, 62 Persian, 63 Dutch 64 ) and Paediatric Pain Profile (PPP) (Brazilian Portuguese 65 ). These articles are summarized in Table S4.…”
Section: Search Resultsmentioning
confidence: 99%
“…Treten neuerlich Schmerzen Tab. 2 Scores und Skalen für verbal und kognitiv eingeschränkte Patienten ECPA-2 (L'echelle comportementale pour personnes agées non communicantes) [115] BISAD (Beobachtungsinstrument für das Schmerzassessment bei alten Menschen mit Demenz), die deutsche Fassung von ECPA [46] BESD (Beurteilung von Schmerz bei Demenz), die deutsche Fassung der PAINAD-Scale [20,163] Doloshort-Skala, deutsche Fassung [96] Face Legs Activity Cry and Consolability-revised (FLACC-r) [104] auf, muss auch die Schmerzerfassung wieder regelmäßig durchgeführt werden [32,141] [92].…”
Section: Schmerzerfassungunclassified